Literasi Digital sebagai Moderasi Pengaruh Digital Marketing dan Lifestyle terhadap Keputusan Pembelian pada Marketplace Online - Rosalia Irawaty; Ana Fitriyatul Bilgies; Abdul Latif; Muhammad Aqshel Revinzky; Eva Yuniarti Utami (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Technological developments are currently experiencing very rapid progress, including in the fields of economics and marketing. The internet is an information mechanism that provides advice or facilities to obtain important data that is needed. Advances in the field of information and communication innovation, the world feels like there are no more boundaries, distance, and time. This study aims to determine digital literacy as a moderation of the influence of digital marketing and lifestyle on purchasing decisions in online marketplaces. The current analysis uses a quantitative approach. The population of this study are consumers who have shopped online. Samples were taken from this population, and the selection of this research sample was determined by random sampling to produce a sample of 150 respondents. Based on the results of the analysis, the results of this study found that digital marketing and lifestyle influence purchasing decisions in online marketplaces. Digital literacy is able to moderate digital marketing and lifestyle on purchasing decisions in online marketplaces.